If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + x = -3x + 55 Reorder the terms: 7 + x = 55 + -3x Solving 7 + x = 55 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 7 + x + 3x = 55 + -3x + 3x Combine like terms: x + 3x = 4x 7 + 4x = 55 + -3x + 3x Combine like terms: -3x + 3x = 0 7 + 4x = 55 + 0 7 + 4x = 55 Add '-7' to each side of the equation. 7 + -7 + 4x = 55 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = 55 + -7 4x = 55 + -7 Combine like terms: 55 + -7 = 48 4x = 48 Divide each side by '4'. x = 12 Simplifying x = 12
| 6m-11.6=4m+8.2 | | 6*(1/7) | | 1.6(2.8)3x=6(4.5)x | | 5/3b=20 | | 6*1/7 | | (3-6i)-(4+5i)-(-5+i)= | | 4x+20=6x+200 | | 4x+9x+7=0 | | 2s=-3 | | X^3+3x^2+2x=504 | | 5x+15=3x-7 | | 15x-6=7x+10 | | y-2/6=y+1/15 | | 2(3x-2)=164 | | 7/10-1/6 | | 344.2x+23.2x+129.32=124.2x-723.2 | | 94.50x1/2 | | 5y-5-4y=7-6 | | 7-b=13 | | 4/7(-2) | | 16x+15=8x+45 | | X+6+5-2x=5+5x-9+3 | | 8-2(4-x)=14 | | 4(y-3)=5(y-1) | | 1.5d+3.25=1+2.25 | | 4x-7=7x-7 | | 7.32x-9.10=2.75x-18.23 | | 3np=r | | 3(2x-3)=-2x-1 | | 6x+10=2(x-1) | | r=3np | | y=-x-10x-21 |